Temporal soliton: Generation and applications in optical communications - Amiri, I.S.; Alavi, S.E.; Supa'at, A.S.M.; Ali, J.; Ahmad, Harith (Penerbit UTM Press, 2016)
In general, the temporal and spectral shape of a short optical soliton pulse does not change during propagation in a nonlinear medium due to the Kerr effect which balances the chromatic dispersion. Microring resonators (MRRs) can be used to generate chaotic signals. The smaller MRR is used to form the stopping and filtering system. The employed optical material was InGaAsP/InP, which is suitable for use in the practical devices and systems. The tuning and manipulation of the bandwidth of the soliton signals is recommended to control the output signals. The MRRs can be applied to produce ultra-short pulses, where the medium has a nonlinear condition, thus, using of soliton laser becomes an interesting subject. Therefore, an ultra-short pulse in the scope of pico and femtoseconds soliton pulses can be utilized for many applications in engineering communications. In order to obtain smaller bandwidth of the optical soliton pulses, we propose integrating series of MRRs. In this study, 5 fs soliton pulse could be generated using a series of five MRRs. The soliton signals experience less loss during the propagation, where they are more stable compared to normal conventional laser pulses. Using the series of MRRs connected to an add/drop system, shorter soliton bandwidth and highly multi soliton pulses can be obtained. Therefore, generation of ultra-short multi picosecond (1.2 and 1.3 ps), could be performed, where the radius of the add/drop system has been selected to 50 and 300 μm respectively.